Fractal Analysis of the Long-Term Memory in Precipitation over Benin (West Africa) - Agbazo, Médard; KOTO N'GOBI, GABIN (My University, 2019)
+is study analyzed the long-term memory (LTM) in precipitation over B´enin synoptic stations from 1951 to 2010 using the detrended fluctuation analysis (DFA) method. Results reveal the existence of positive long-term memory characteristic in rainfall field. DFA exponent values are different regarding the concerned synoptic stations, reflecting the effect of geographical position and climate on the LTM. +ese values were related to the type of climate. +e best DFA1-4 method depends on the geographical position of the studied station. However, DFA2 is generally the best in terms of spatial average from DFA1 to DFA4. In B´enin synoptic stations, except the Parakou station, the long-term temporal correlations are systematically the source of multifractality in rainfall. Except Natitingou, the strength of long-term memory characteristic decreases each twenty years in the study period. Considering the fractal approach, our results show that the subperiod 1991–2010 is not really a transition period as shown before. +us, the drought is prolonging until 2010. So, fractal theory reveals more Benin climatic characteristics.
Keywords: Long term memory; Fractal Analysis; MFDFA; Benin